Process of Economic Integration of Poland in Spatial Dimension, with Focus on Western and Northern Territories and the Traditionally Polish Territories (1945-1989) - Kociszewski, Jerzy (Studia Historiae Oeconomicae, 2006)
Literature dealt with the problem of integration of Poland after the 1939-1945 war either rarely or transitorily, both as regards its essence and its various demonstrations. The reasons why it was so were manifold: The essence and scope of integration should be studied according to some methodologies, while there were many of its models and typologies available; integration is subject to constant verifications and redefinitions; moreover, its scope and aims have not been defined yet. The economic strategy of development accepted in the post-war Poland was closely connected with spatial integration. This integration became particularly im- portant in the process of merging the regained western and northern territories (further referred to as WNT) with the traditionally Polish territories (TTP), and it was much affected by political conditions. In subsequent stages of Poland's development, the approach to integration and its interpretation were closely dependent on the objectives set by the command-distributive system.